Find the real solution(s) of sqrt(3-x)-sqrt(x+1) > 1/3√3−x−√x+1>13 ?
1 Answer
Explanation:
First find values of
sqrt(3-x)-sqrt(x+1) = 1/3√3−x−√x+1=13
Squaring both sides (which may introduce spurious solutions), we get:
(3-x)-2sqrt((3-x)(x+1))+(x+1) = 1/9(3−x)−2√(3−x)(x+1)+(x+1)=19
which simplifies to:
4-2 sqrt(3+2x-x^2) = 1/94−2√3+2x−x2=19
Multiply both sides by
36-18 sqrt(3+2x-x^2) = 136−18√3+2x−x2=1
Hence:
35 = 18 sqrt(3+2x-x^2)35=18√3+2x−x2
Square both sides to get:
1225 = 324(3+2x-x^2) = 972+648x-324x^21225=324(3+2x−x2)=972+648x−324x2
Rearrange to get:
324x^2-648x+253 = 0324x2−648x+253=0
Divide through by
0 = x^2-2x+253/324 = (x-1)^2-71/3240=x2−2x+253324=(x−1)2−71324
Hence
Note that if
sqrt(3-x)-sqrt(x+1) < 0√3−x−√x+1<0
If
sqrt(3-x)-sqrt(x+1) = sqrt(2+sqrt(71)/18)-sqrt(2-sqrt(71)/18) > 0√3−x−√x+1=√2+√7118−√2−√7118>0
and we find:
(sqrt(3-x)-sqrt(x+1))^2 = (sqrt(2+sqrt(71)/18)-sqrt(2-sqrt(71)/18))^2(√3−x−√x+1)2=⎛⎝√2+√7118−√2−√7118⎞⎠2
color(white)((sqrt(3-x)-sqrt(x+1))^2) = (2+sqrt(71)/18)-2sqrt((2+sqrt(71)/18)(2-sqrt(71)/18))+(2-sqrt(71)/18)(√3−x−√x+1)2=(2+√7118)−2 ⎷(2+√7118)(2−√7118)+(2−√7118)
color(white)((sqrt(3-x)-sqrt(x+1))^2) = 4-2sqrt(4-71/324)(√3−x−√x+1)2=4−2√4−71324
color(white)((sqrt(3-x)-sqrt(x+1))^2) = 4-2sqrt(1225/324)(√3−x−√x+1)2=4−2√1225324
color(white)((sqrt(3-x)-sqrt(x+1))^2) = 4-2*35/18(√3−x−√x+1)2=4−2⋅3518
color(white)((sqrt(3-x)-sqrt(x+1))^2) = 36/9-35/9(√3−x−√x+1)2=369−359
color(white)((sqrt(3-x)-sqrt(x+1))^2) = 1/9(√3−x−√x+1)2=19
So this is a valid solution.
Now if